PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING BERBASIS MEDIA WORDWALL TERHADAP KEMAMPUAN PROBLEM SOLVING SISWA KELAS VI PADA PEMBELAJARAN MATEMATIKA DI MI IBROHIM ASSAMARQONDI TP 2025/2026 - Vivi Nur Aisyah; Supriyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low problem-solving ability of students in mathematics learning at the Madrasah Ibtidaiyah level. Teacher-centered learning practices often limit students’ opportunities to engage with contextual problems and develop independent problem-solving strategies. Therefore, an innovative learning model supported by digital media is needed to enhance student engagement and learning outcomes. This study aims to examine the effect of the Problem Based Learning model assisted by Wordwall media on the problem-solving ability of sixth-grade students in mathematics learning at MI Ibrohim Assamarqondi in the 2025/2026 academic year.This research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The population consisted of all sixth-grade students of MI Ibrohim Assamarqondi, totaling 28 students. The sample was divided into two groups: the experimental group, which received instruction using the PBL model assisted by Wordwall media, and the control group, which received conventional learning. Data were collected through tests, observations, and documentation. The data were analyzed using statistical techniques to determine differences in students’ problem-solving abilities before and after the treatment.The results are expected to indicate that the implementation of the Problem Based Learning model assisted by Wordwall media has a positive effect on students’ problem-solving abilities. This learning model encourages students to think critically, actively participate in the learning process, and systematically solve mathematical problems.